2021
DOI: 10.1017/s0950268821000923
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of oral contraceptive against Helicobacter pylori infection in US adult females: NHANES 1999–2000

Abstract: Recently, the antibacterial properties of oestrogen and progestogen were discovered. The aim of this study was to find the cross-sectional association between oral contraceptive use and Helicobacter pylori seroprevalence. Data were obtained from the US National Health and Nutrition Examination Survey (NHANES). The H. pylori immunoglobulin G (IgG) enzyme-linked immunosorbent assays were used to categorise participants as seropositive or seronegative. The study population included 799 female participants who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…We believe that the high level of H. pylori infection in the present study population may be related to living in heavy metal-polluted areas. Studies have reported that the BCd and BPb levels, and in particular the Pb levels, were significantly associated with H. pylori seroprevalence among participants under 13 years of age and American adult women [3,32]. Moreover, as indicated by another study, even a small increase in the BPb levels may increase the risk of H. pylori infection [33].…”
Section: Discussionmentioning
confidence: 89%
“…We believe that the high level of H. pylori infection in the present study population may be related to living in heavy metal-polluted areas. Studies have reported that the BCd and BPb levels, and in particular the Pb levels, were significantly associated with H. pylori seroprevalence among participants under 13 years of age and American adult women [3,32]. Moreover, as indicated by another study, even a small increase in the BPb levels may increase the risk of H. pylori infection [33].…”
Section: Discussionmentioning
confidence: 89%
“…Maybe sex hormones were responsible for age-specific differences. Some researches had demonstrated the protective effect of certain steroids against H. pylori infection ( Hosoda et al., 2011 ; Ohtani et al., 2011 ; Fong and Wang, 2021 ). For example, Kouichi Hosoda discovered that the growth of H. pylori could be inhibited by estradiol and progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by P Fong, the protective effect of oral contraceptives against H. pylori infection was investigated. The results indicated that women who were using oral contraceptives had a significantly reduced risk of acquiring H. pylori infection in comparison to those who did not use them ( Fong and Wang, 2021 ). As women reach the age of 40, their levels of free estradiol decline significantly, which weakens the protective effect of hormones on them ( Runolfsdottir et al., 2015 ).This may lead to a more vulnerable state in older women, resulting in greater muscle decline following H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to estrogen, another steroid hormone, progestogen, was also found to exert bacteriolytic effects against H. pylori , stronger than those exhibited by estrogen[ 52 ]. In another study, Fong et al revealed the potential protective effect of oral contraceptives against H. pylori infection using the US National Health and Nutrition Examination Survey dataset[ 53 ]. A recent study found that the nuclear receptor estrogen-related receptor gamma (ESRRG) can affect H. pylori infection-driven gastric cancer.…”
Section: Discussionmentioning
confidence: 99%